A period of transition: a history of Grahamstown, 1902-1918 - Southey, Nicholas (Rhodes University, Faculty of Humanities, Department of History, 1984)
A Period of Transition : A History of Grahamstown 1902-1918 attempts to show that the trends begun in the nineteenth century were confirmed by developments in the first two decades of the twentieth century. In this period, Grahamstown was forced to abandon ideas of economic recovery and political importance, as it adapted to its role in the post-Union dispensation. The city has been firmly grounded in the wider environment, though comparison with towns of similar position and outlook has been impossible because of a lack of source material.4 It is clearly evident that Grahamstown was under pressure from the macrocosm; nonetheless, local initiatives and developments also lent clarity to broader trends. This is particularly clear in the emerging pattern of racial segregation in the City, to cope with the economic and social problems posed by a burgeoning black population. The limited financial resources of a corporation the size of Grahamstown restricted its effectiveness to improve schemes of public works and public health, and further underlined the dependence of the city on the government for assistance. Grahamstown's transition was predominantly one of acceptance of a changed political, social and economic environment.
Keywords: Grahamstown (South Africa) -- History